Sustainable resource management coupled to resilient germplasm to provide new intensive cereal–grain–legume–livestock systems in the dry savanna - Sanginga, Nteranya; Dashiell, Kenton E.; Diels, J.; Vanlauwe, Bernard; Lyasse, O.; Carsky, R.J.; Tarawali, Shirley A.; Asafo-Adjei, B.; Menkir, A.; Schulz, S.; Singh, B.B.; Chikoye, David; et al. (Elsevier, 2003)
Sustainable resource management is the critical agricultural research and development challenge in sub-Saharan Africa. The accumulated knowledge on soil management gathered over the last 10 years, combined with solid crop improvement and plant health research at farmers’ level, has brought us to a stage where we can now address with confidence the intensification of cereal–grain–legume-based cropping systems in the dry savanna of West Africa in a sustainable and environmentally positive manner. Two sustainable farming systems that greatly enhance the productivity and sustainability of integrated livestock systems have been developed and implemented in the dry savanna of Nigeria. These are: (i) maize (Zea mays L.)–promiscuous soybean [Glycine max (L.) Merr.] rotations that combine high nitrogen fixation and the ability to kill large numbers of Striga hermonthica seeds in the soil; and (ii) miflet [Eleusine coracana (L.) Gaerth] and dual-purpose cowpea [Vigna unguiculata (L.) Walp.]. Improvement of the cropping systems in the dry savanna has been driven by the adoption of promiscuously nodulating soybean varieties (in particular TGx 1448-2E) and dual-purpose cowpea. The rate of adoption is very high, even in the absence of an efficient seed distribution system. The number of farmers cultivating the improved varieties increased by 228% during the last 3 years. Increased production of promiscuous soybean has been stimulated by increased demand from industries and home utilization. Production in Nigeria was estimated at 405,000 t in 1999 compared to less than 60,000 t in 1984. Economic analysis of these systems shows already an increase of 50–70% in the gross incomes of adopting farmers compared to those still following the current practices, mainly continuous maize cultivation. Furthermore, increases in legume areas of 10% in Nigeria (about 30,000 ha in the northern Guinea savanna) and increases of 20% in yield have translated into additional fixed nitrogen valued annually at US$ 44 million. This reflects, at the same time, an equivalent increase in land-use productivity, and with further spread of the improved crops, there are excellent prospects for additional economic and environmental benefits from a very large recommendation domain across West Africa.